Keluarnya Britania Raya dari Keanggotaan Uni Eropa dan Implikasinya Bagi Perekonomian - Danial Darwis; Theyana Howay (Universitas Warmadewa, 2021)
In June 2016, British citizen voted to leave the European Union, a phenomenon known as Britain Exit for short for Brexit. This paper aims to examine the influence of British Exit (Brexit) on the UK economy, namely Gross National Income (GNI) and Gross National Product (GNP) based on exports-imports, Foreign Direct Investment (FDI) and employment. The referendum showed that more than fifty per cent of British citizen voted out of the European Union. Post British Exit (Brexit) politics. The Brexit referendum can be seen from the fundamental reasons, namely the regulation of the UK's own economic market and immigration issues. That cost the UK more because of the lost preferential access to the huge EU market. This paper analyzes using the theory of economic growth and the concept of national interest. The research method used is a qualitative research method, with secondary data sources obtained from online news, books, journals, and other written sources. The data collection technique used is library research, with data analysis techniques starting from data reduction, data presentation, to drawing conclusions. The results and discussion of this paper are that the UK's national interest in the form of ownership issues is the reason for Brexit, even though this has an impact on the decline in economic growth experienced by the UK.